2016
DOI: 10.1111/clr.12756
|View full text |Cite
|
Sign up to set email alerts
|

Validation of value of actual micromotion as a direct measure of implant micromobility after healing (secondary implant stability). An in vivo histologic and biomechanical study

Abstract: As VAM showed to be statistical correlated to the other parameters of osseointegration, it may be used to clinically check the amount of implant osseointegration, secondary stability and CBL. Future studies are needed to confirm these results moreover. An instrument to measure VAM in the oral cavity still needs to be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…In other clinical studies in which a non-functional loading with no occlusal contacts was used, similar outcomes were also reported. 32,33 In this study, we used In recent studies, it was reported that RFA was a reliable tool for assessment of implant stability and ISQ value significantly correlated with other implant stability parameters such as insertion torque value, 11,19 bone density, 11,21 actual micro-motion value, 34 and fractal analysis. 35,36 However, controversial results were also reported about the reliability of ISQ for the assessment of implant stability.…”
Section: Discussionmentioning
confidence: 99%
“…In other clinical studies in which a non-functional loading with no occlusal contacts was used, similar outcomes were also reported. 32,33 In this study, we used In recent studies, it was reported that RFA was a reliable tool for assessment of implant stability and ISQ value significantly correlated with other implant stability parameters such as insertion torque value, 11,19 bone density, 11,21 actual micro-motion value, 34 and fractal analysis. 35,36 However, controversial results were also reported about the reliability of ISQ for the assessment of implant stability.…”
Section: Discussionmentioning
confidence: 99%
“…[38] The significant decrease in retention of the overdentures in all patients after 12 months of clinical use, dictated replacement of the wearied pink nylon inserts with new ones utilizing the insertion tool. [39] The significant increase in the mean bone height measurements in both groups, indicating increased crestal bone resorption in the first six months compared to those measurements from six to twelve months, which might be explained by the continuous remodeling process of bone surrounding the implant resulting in bone resorption, followed by bone deposition. [40].…”
Section: Discussion Of Resultsmentioning
confidence: 98%
“…In the laboratory setting, macromotion may lead to implant failure, while micromotion is beneficial to bone‐implant integration. Implant micromotion is equally important for stable OI, whereby micromotions up to 30 µm enhance OI, and micromotions greater than 150 µm inhibit it …”
Section: Current Challengesmentioning
confidence: 99%